Monitoring of the phytosanitary condition of cucumber plantings under greenhouse conditions and features of the development of the Melon Aphid (Aphis gossypii Glover) - Tkalenko, H.; Havryliuk, Ya. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To monitor the phytosanitary condition of cucumber crops under greenhouse conditions, identify the species composition of dominant pests, determine the period of emergence and development of the melon aphid (Aphis gossypii Glov.), and assess its population density. Methods. The field method included monitoring to detect and study the seasonal dynamics of pest populations, as well as route inspections of cucumber crops. The research was conducted at the Laboratory of Microbiological Plant Protection of the Institute of Plant Protection of the National Academy of Agrarian Sciences of Ukraine (NAAS) and in private film greenhouses (Kyiv region, Brovary district). Cucumber hybrids of both foreign and Ukrainian selection were used — Rodnychok F1, Kurazh F1, and Ekol F1. To study the development and population dynamics of the melon aphid on cucumbers under greenhouse conditions, systematic observations and counts of its population density were carried out. Results. During the monitoring of cucumber plants in greenhouses in 2023—2025, it was found that throughout the vegetation period (spring–summer crop rotation), the crops were infested by the melon aphid (Aphis gossypii Glov.), spider mite (Tetranychidae), thrips (Thrips spp.), seedcorn maggot (Delia platura Mg.), and several polyphagous pests. Throughout the study years, the dominant pest species was the melon aphid (Aphis gossypii Glov.), accounting for 40.3—48.3% of the total pest complex. The spider mite (Tetranychidae) made up 38.5%. Cucumber plants were also infested by thrips, predominantly the tobacco thrips (Thrips tabaci Lind.) — 10%; seedcorn maggot (Delia platura Mg.) — 0.2—0.3%; and other polyphagous pests — 2.7%. It was determined that the flight of winged aphid migrants from overwintering sites began in early April, with mass larval hatching occurring at the beginning of the third ten-day period of April. The population density of the melon aphid increased throughout the cucumber vegetation period, reaching a maximum of 37 individuals per plant. Conclusions. The conducted monitoring of phytophagous pests on cucumbers under greenhouse conditions showed that the dominant species is the melon aphid (Aphis gossypii Glov.), which forms the highest population density among other species. Determining the period of its flight from overwintering sites, the beginning of plant colonization, and the dynamics of population density makes it possible to timely predict pest emergence and determine optimal periods for preventive and protective measures. The obtained results have practical significance for the development of an integrated pest management (IPM) system for vegetable crops under greenhouse conditions. They provide a scientific basis for regulating aphid populations considering biotic and abiotic factors, contributing to reduced pesticide load, enhanced biological control efficiency, and stabilization of the phytosanitary condition of greenhouse agrocenoses.